Study on the effect of radiation-degraded β-glucan on body weight gain and blood biochemical indexes in mice - Long, Nguyễn Thành; Xô, Dương Hoa; Luân, Lê Quang (Vietnam Journal of Biotechnology, 2016)
The suspension solution containing 10% water-insoluble β-glucan extracted from yeast cell wall was irradiated by gamma rays from a Co-60 source for degradation. The water-soluble β-glucan products with molecular weight (Mw) of about 30.5, 24.9 and 10.8 kDa were successfully prepared from the samples irradiated at the doses of 100, 200 and 300 kGy, respectively. The obtained water-soluble β-glucan products were tested in mice for examination of their effect on the weight gain, feed conversation rate and blood chemistry indexes. The results after 4 weeks testing indicated that the oral supplementation of all water-soluble β-glucan samples prepared by gamma rays Co-60 irradiation method promoted the increase of body weight as well as the efficiency in converting the feed mass into the weight gain in the tested mice. In addition, β-glucan samples also reduded some contents of blood biochemistry indexes such as of glucose, urea, total protein, triglyceride and cholesterol in tested mice. The supplementation by 2 mg per mouse water-soluble β-glucan product with Mw ~ 24.9 kDa prepared by gamma irradiation at 200 kGy enhanced 16.1% the body weight and decresed 13.3% the feed conversation rate for the tested mice. The results on the blood biochemistry indexes also indicated that this β-glucan product reduced the contents of glucose, urea, total protein, triglyceride, and cholesterol in blood of tested mice by 27.1, 67.3, 56.0, 57.4 and 51.5%, respectively, compared to those in blood of the control ones. Thus, the low Mw and water-soluble β-glucan prepared by irradiation method can be applied as a potential material for production of the functional foods.